Using GeoGebra (3D With Jogl2) In Geometric Constructions (Eurasian Journal of Learning and Academic Teaching, 2024)
Construction problems have always been an important part in learning Geometry. The following article is a new way to use technology to create geometric constructions instead of using an old-school ruler and compass. This will help teachers incorporate technology in the classroom and save time and materials in the process.